Impact of Cathepsin L Inhibition in SARS-CoV-2 Infection and Potential Therapeutic Interventions - Azhar, Muteeba; Irshad, Asma; Zubair, Ansar; Batool, Tahira; Maqsood, Ammara; Saleem, Mehreen; Bashir, Rida (BioScientific Review, 2025)
Background. The global COVID-19 pandemic caused by SARS-CoV-2 has prompted the urgent development of effective therapeutic strategies since its emergence in China. Cathepsin L is a lysosomal cysteine protease that plays a pivotal role in the entry of SARS-CoV-2 into the host cell. It follows an endocytic pathway that triggers the fusion of host and viral cell membranes. Mechanism. Viral RNA is released during this phase and enters the host’s cytoplasm through cleavage at S1/S2 or S2′ sites of the Spike glycoprotein of SARS-CoV-2. A study showed K790 as the potential cleavage site for cathepsin L. It is located near the S2′ site on the same loop. Its potential for proteolysis indicates its capacity to induce structural modifications analogous to S2′ cleavage, ultimately activating membrane fusion to allow the entry of the virus. The inhibitors of cathepsin L have emerged as effective drug targets in antiviral therapy. Conclusion. This study aims to elaborate on the potential role of cathepsin L in SARS-CoV-2 infection during its entry into the host cells and also explores its functional and structural biology. Additionally, it highlights several promising inhibitory compounds including K11777, E64d, SDI 26681509, CID23631927, and Gallinamide A, which are effective in treating the SARS-CoV-2 infection. US Food and Drug Administration (FDA) approved drugs including amantadine, teicoplanin, and chloroquine have the potential to combat the SARS-CoV-2 infection. Understanding the significance of cathepsin L and the use of its inhibitors as therapeutic agents may open new opportunities for developing effective treatments for SARS-CoV-2.